1971
DOI: 10.1002/jmor.1051340402
|View full text |Cite
|
Sign up to set email alerts
|

The number of centrioles in insect sperm: A study in two kinds of differentiating silkworm spermatids

Abstract: The typical eupyrene and atypical apyrene cycles of sperm differentiation in Bombyx mori were studied, with special attention to centriole number and behavior. Contrary to other reports, there is always only one centriole in the differentiating and in the mature sperm, thus confirming our previous findings that insect sperm has one centriole at the base of the flagellum, in contrast to two centrioles found in many other groups of animals. This numerical difference is discussed in an evolutionary context.We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Eupyrene and apyrene spermatogenesis differ profoundly but their respective morphogenetic pathways are consistent, showing only minor variations among the diverse species. Although the general pattern of differentiation leading to the two types of spermatozoa have been worked out in some detail [4][5][6][7], the regulation of this dichotomy is still unclear [ 8]. 114 The conspicuous cytological events of the eupyrene spermatogenesis precede those of the apyrene spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Eupyrene and apyrene spermatogenesis differ profoundly but their respective morphogenetic pathways are consistent, showing only minor variations among the diverse species. Although the general pattern of differentiation leading to the two types of spermatozoa have been worked out in some detail [4][5][6][7], the regulation of this dichotomy is still unclear [ 8]. 114 The conspicuous cytological events of the eupyrene spermatogenesis precede those of the apyrene spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This centriole forms the flagellum and is therefore the homolog to the vertebrate distal centriole. During spermatid differentiation ( Figure 2A), a structure, called the centriolar adjunct (CA), appears transiently around this centriole (Friedlander and Wahrman 1971;Tates 1971;Tokuyasu 1975a,b;Wilson et al 1997). The centriolar adjunct is a very dynamic structure, which shrinks during spermatid differentiation to form a collar around the distal centriole and then disappears (Tates 1971;Wilson et al 1997).…”
mentioning
confidence: 99%
“…Previous studies on the testicular sperm of Lepidoptera were reported by Zylberberg (1963), Smith (1968), Phillips (1970a,b), Riemann (1970), Friedlander & Wahrman (1971), and Friedlander & Hauschtech-Jungen (1982) and by several studies reported in Baccetti (1970): Throughout the process of sperm maturation, the MDs are a prominent feature. In the youngest spermatid cysts, the cytoplasm contains numerous mitochondria.…”
Section: Discussionmentioning
confidence: 88%